Criminological Analysis of Sexual Slavery - Mehdi Zakavi (Journal of Global Pharma Technology, 2018)
Sexual slavery as an organized crime in the 21st century has become a proplem for human societies and is expanding and due to the lack of strong implementation guarantee and comprehensive and restricted rules in order to give an answer to these uncontrolling conditions and disrespects to the extent of value and dignity of human, this phenomenon of the century is rising day by day. This study is aimed to investigate the reasons and factors of prevalence of sexual slavery in the present century which has been studied and analyzed by library and internet studies and news sites. According to obtained results several reasons have caused this global scourge to be occurred such as problems and poverty, unwariness, changing position and lack of prosecution due to the fear of prestige and such factors from the side of victims themselves, low cost, high profit of this dirty business, not getting caught the perpetrators of these crimes and their enjoyment of broad support. This dilemma, which is hated by all international societies, is sharply growing and is considered as a very important source of income. There is a need for a strong determination at national and international levels by concluding protocol and law and implementation guarantee and informing and training individuals through mass media as well as to support the victims of these crimes in order to serious fight agaist this problem.Keywords: Sexual slavery, Organizing, Crime against humanity, Human trafficking.